Constraining X-ray-Induced Photoevaporation of Protoplanetary Disks Orbiting Low-Mass Stars. Issue Volume 10:Issue S314(2015) (November 2015) - Punzi, Kristina M.; Kastner, Joel H.; Rodriguez, David; Principe, David A.; Vican, Laura
Abstract: Low-mass, pre-main sequence stars possess intense high-energy radiation fields as a result of their strong stellar magnetic activity. This stellar UV and X-ray radiation may have a profound impact on the lifetimes of protoplanetary disks. We aim to constrain the X-ray-induced photoevaporation rates of protoplanetary disks orbiting low-mass stars by analyzing serendipitous XMM-Newton and Chandra X-ray observations of candidate nearby (D < 100 pc), young (age < 100 Myr) M stars identified in the GALEX Nearby Young-Star Survey (GALNYSS).